Bioequivalence Evaluation Between Acarbose and Metformin Fixed‐Dose Combination and Corresponding Individual Components in Healthy Chinese Male and Female Subjects. Issue 2 (13th July 2021) - Liu, Chao; Cleton, Adriaan; Sui, Yubin; Liu, Yuwang; Li, Jinyi; Yuan, Fei; Sheng, Lei; Xu, Hongrong; Li, Xuening
Abstract: Acarbose and metformin have been recommended both as monotherapy and add‐on therapy in type 2 diabetes mellitus. A novel fixed‐dose combination (FDC) of acarbose and metformin has been developed to improve compliance and patient adherence to therapy. The current study investigated the bioequivalence (BE) between acarbose/metformin FDC (50 mg/500 mg) with corresponding loose combination of individual components under fasting conditions in healthy Chinese male and female subjects, using a randomized, 2‐period, 2‐way crossover study design. Pharmacodynamic parameters of serum glucose ratio between treatment day and baseline (ratio of maximum concentration [Cmax ], day 1/Cmax, day –1 and ratio of area under the concentration‐time curve [AUC] from time 0 to 4 hours, day 1/AUC from time 0 to 4 hours, day –1) were used as the primary variables to evaluate BE of acarbose. Pharmacokinetic parameters Cmax, AUC from time 0 to the last data point greater than the lower limit of quantification, and AUC were used to evaluate BE of metformin. The results showed that the 90% confidence intervals of the ratios of all primary target variables including ratio of Cmax, day 1/Cmax, day –1 and ratio of AUC from time 0 to 4 hours, day 1/AUC from time 0 to 4 hours, day –1 for acarbose, and Cmax, AUC from time 0 to the last data point greater than the lower limit of quantification, and AUC for metformin all fell within the acceptance limits of 0.8 to 1.25. Thus, BE between 50‐mg acarbose and 500‐mg metformin as an FDC and loose combination was established. Furthermore, different kinds of exploratory pharmacodynamic parameters (based on either serum glucose or insulin) including several newly proposed parameters were also investigated for acarbose BE evaluation in this study, and inconsistent results were observed.